Micro-nano dual-scale synergistically enhanced MXene-based conductive composite film and preparation method thereof

By doping PPy on MXene nanosheets and combining with nanofiber membranes and MOF microspheres, a MXene-based conductive composite film with micro-nano dual-scale synergistic enhancement is solved, and high-performance electromagnetic shielding and hydrophobic effects are achieved.

CN120042064APending Publication Date: 2025-05-27ZHONGYUAN ENGINEERING COLLEGE

Patent Information

Application Number
CN202510183843.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

MXene has poor structural stability and low bonding fastness to the substrate, resulting in the conductive layer being easily oxidized and the electromagnetic shielding performance is poor.

Method used

Using a micro-nano dual-scale synergistic enhancement method, pyrrole monomer is combined with MXene nanosheets in MXene solution to form MXene nanosheets doped inside PPy, and load it onto the nanofiber membrane. Then, it is combined with MOF microspheres and hydrophobic agents through vacuum-assisted suction filtration technology to construct a hydrophobic conductive composite membrane.

Benefits of technology

The stability of MXene nanosheets and bond fastness with the substrate are improved, and the electromagnetic shielding, hydrophobic properties and soft foldable properties of the composite film are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120042064A_ABST
    Figure CN120042064A_ABST
Patent Text Reader

Abstract

The invention provides a micro-nano dual-scale synergistically enhanced MXene-based conductive composite film and a preparation method thereof, belongs to the technical field of multifunctional electromagnetic shielding composite materials, and aims to solve the technical problems that MXene is poor in structural stability and low in binding strength with a base material. The preparation method of the composite membrane comprises the following steps: dropwise adding a pyrrole monomer into an MXene solution to prepare an MXene nanosheet internally doped with PPy, and loading the MXene-PPy nanosheet onto a nanofiber membrane to prepare an MXene-based nanofiber conductive membrane; the MOF microspheres and a hydrophobic agent are mixed to prepare a hydrophobic solution, and the MXene-based nanofiber conductive film is soaked in the hydrophobic solution. The micro-nano dual-scale synergistically enhanced MXene-based conductive composite film prepared by the invention has excellent electromagnetic shielding performance, good hydrophobic property, light weight, softness and foldability, and can be flexibly applied to electromagnetic shielding in various complex environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of multifunctional electromagnetic shielding composite materials, and particularly relates to a conductive composite film. Background Art

[0002] With the rapid development of science and technology and the wide application of electronic and electrical equipment, electromagnetic radiation interference has become an environmental pollution problem that cannot be ignored in commercial, industrial, military and other fields. Therefore, metal materials, conductive polymer materials, carbon-based materials such as carbon nanotubes (CNTs) and graphene (GR) have been widely used in the field of electromagnetic shielding. However, metal materials such as copper are relatively expensive, iron is prone to rust, steel has too high a density, and problems such as oxidation and corrosion are likely to occur. Conductive polymer materials require relatively thick coatings to achieve electromagnetic shielding effects. In addition, carbon-based materials lack hydrophilic functional groups, and the presence of an inert surface makes their dispersion difficult, restricting their application. Since the first report of two-dimensional transition metal (MXene) for electromagnetic interference shielding in 2016, MXene has taken a leading position in lightweight electromagnetic shielding materials due to its many advantages such as excellent shielding performance, outstanding metallic conductivity, and low density. However, pure MXene films have poor mechanical properties and poor structural stability, making it difficult to meet their practical applications as electromagnetic shielding materials. MXene has good hydrophilicity and excellent film-forming properties, indicating that MXene can prepare conductive thin films or coating materials by means of dip coating, spraying, layer-by-layer assembly, vacuum-assisted filtration, etc. without sacrificing its own conductivity. For example, patent publication number CN114150496A discloses a flexible nanofiber membrane with electromagnetic shielding and piezoresistive sensing properties and its preparation method, belonging to the technical field of multifunctional material preparation. First, a polymer nanofiber membrane is obtained through the electrospinning process, and then an MXene@Fe 3 O 4 dispersion liquid is prepared, and then a polymer nanofiber membrane with good hydrophilicity is prepared by dopamine modification treatment, and the target fiber membrane is obtained by combining the spraying process. However, the structural stability of the MXene conductive layer and the bonding strength with the substrate are also important issues that need to be considered. Summary of the Invention

[0003] Aiming at the technical problems of poor structural stability of MXene, low bonding strength with the substrate, and poor electromagnetic shielding performance caused by easy oxidation of the MXene conductive layer, the present invention proposes a micro-nano dual-scale synergistically enhanced MXene-based conductive composite film and its preparation method, which has excellent electromagnetic shielding performance, good hydrophobic characteristics, and lightweight, soft and foldable characteristics. The constructed hydrophobic conductive composite film realizes high-performance EMI shielding at an ultra-thin thickness.

[0004] In order to achieve the above object, the technical solution of the present invention is realized as follows:

[0005] A micro-nano dual-scale synergistically enhanced MXene-based conductive composite membrane, and the preparation method comprises the following steps:

[0006] (1) Drop pyrrole monomers into an MXene solution to prepare MXene nanosheets doped with PPy inside, denoted as MXene-PPy nanosheets;

[0007] (2) Load the MXene-PPy nanosheets onto a nanofiber membrane to prepare an MXene-based nanofiber conductive membrane;

[0008] (3) Mix MOF microspheres with a hydrophobic agent to prepare a hydrophobic solution, and immerse the MXene-based nanofiber conductive membrane in the hydrophobic solution to prepare a micro-nano dual-scale synergistically enhanced MXene-based conductive composite membrane with hydrophobic effect.

[0009] The mass ratio of the pyrrole monomers to MXene is 1:(0.5 - 2); the concentration of MXene in the MXene solution is 0.01 - 0.1 g / ml.

[0010] The nanofiber membrane is any one of polyacrylonitrile, polyurethane or thermoplastic polyurethane nanofiber membranes.

[0011] The nanofiber membrane is a nanofiber membrane modified with polydopamine, and the modification method is: soak the nanofiber membrane in a solution containing dopamine (DA) to cause the polymerization reaction of DA.

[0012] The preparation method of the solution containing DA is: dissolve the hydrochloride of tris(hydroxymethyl)aminomethane and DA with a mass ratio of 3:5 in deionized water, then dissolve the silane coupling agent (APTES) in an ethanol solution, add them to the above deionized water together, and mix evenly to prepare the solution containing DA.

[0013] The concentration of DA in the solution containing DA is 0.1 - 0.5 wt%, and the mass ratio of DA to APTES is 1:(1 - 3); the conditions of the polymerization reaction are pH = 8 - 9 and the polymerization time is 0 - 12 h.

[0014] In the step (2), the MXene-PPy nanosheets are loaded on at least one side of the nanofiber membrane; the loading method is suction filtration or coating.

[0015] In step (2), the MXene-PPy nanosheets are vacuum-assisted filtered on both sides of the nanofiber membrane. The preparation method is as follows: The MXene-PPy nanosheets are dispersed in a solvent to prepare a suspension. The nanofiber membrane is placed on a hydrophilic support membrane for vacuum-assisted filtration, and the MXene-PPy nanosheets are deposited on one side of the nanofiber membrane to form an upper conductive layer. Then, the nanofiber membrane is flipped and placed on a hydrophobic support membrane for vacuum-assisted filtration, and the MXene-PPy nanosheets are deposited on the other side of the nanofiber membrane to form a lower conductive layer.

[0016] The concentration of the suspension is 0.005 - 0.1 g / ml.

[0017] The MOF microspheres are Ni-Co MOF microspheres; the hydrophobic agent is any one of a silicon-containing hydrophobic agent or a fluorine-containing hydrophobic agent; the silicon-containing hydrophobic agent is polydimethylsiloxane; the fluorine-containing hydrophobic agent is 1H,1H,2H,2H-perfluorodecanethiol (PFDT).

[0018] The concentration of the hydrophobic agent in the hydrophobic aqueous solution is 0.5 - 4 wt%, and the concentration of the MOF microspheres is 0 - 2 mg / m; preferably, the concentration of the MOF microspheres is 0.1 - 2 mg / ml. The solvent in the hydrophobic aqueous solution is any one of n-heptane, methanol, ethanol, isopropanol, toluene, xylene, and dichloromethane.

[0019] The beneficial effects of the present invention are as follows:

[0020] (1) The present invention uses the weak acidity of the MXene solution to prepare MXene nanosheets with internal doping of PPy, improving the stability of the MXene nanosheets.

[0021] (2) The present invention combines the MXene nanosheets with synergistic enhancement inside PPy and the nanofiber membrane through vacuum-assisted filtration technology to construct a sandwich-structured MXene-based conductive composite membrane. Then, the Ni-Co MOF is coupled and compounded with a silicon-containing hydrophobic agent to construct a hydrophobic surface, and a MXene-based multifunctional conductive composite membrane with micro-nano dual-scale synergistic enhancement modification is prepared, endowing the composite membrane with excellent EMI shielding performance, electro-optical and thermal properties, and good hydrophobic properties, making it flexibly applicable to various complex environments.

[0022] (3) The present invention uses the nanofiber membrane as a substrate, and improves the structural stability of the MXene-based material by modifying the inside and outside of the MXene nanosheets, endowing it with good environmental adaptability, which is conducive to the integrated, portable, flexible, and intelligent development of the MXene-based conductive material.

[0023] (4) The hydrophobic and conductive composite film prepared by the present invention based on the layer-by-layer assembly strategy and vacuum filtration technology realizes high-performance EMI shielding at an ultra-thin thickness, providing a research idea for the structural stability design of subsequent MXene-based composite films. Description of the Drawings

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0025] Figure 1 Schematic diagram of the preparation process of the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film prepared by the present invention; (a) MXene-PPy nanosheets; (b) dual-scale synergistically enhanced MXene-based conductive composite film.

[0026] Figure 2 SEM images and antibacterial property characterization of the MXene-PPy nanosheets prepared by the present invention; (a) SEM image of MXene; (b) XRD patterns of MXene and MXene-PPy; (c-d) SEM images of MXene-PPy nanosheets; (e) antibacterial property characterization.

[0027] Figure 3 Thermal performance curve of the MXene-PPy nanosheets prepared by the present invention; (a) TG curves of MXene before and after PPy doping modification; (b) DSC curves of MXene before and after PPy doping modification.

[0028] Figure 4 Morphology characterization and surface chemical element characterization of the Ni-Co MOF prepared by the present invention; (a-b) SEM images of the Ni-Co MOF prepared by the present invention; (c-d) XRD and XPS curves of the Ni-Co MOF prepared by the present invention.

[0029] Figure 5 Morphology characterization and hydrophilic-hydrophobic property changes of the MXene-based conductive composite film before and after hydrophobic modification by the present invention; (a-b) SEM images of the PP@MXene-P composite film; (c) contact angle change diagram of the upper and lower surface conductive layers of the PP@MXene-P composite film; (d-e”) SEM images of the PP@MXene-P@PDMS-NC composite film after hydrophobic agent modification; (f) contact angle change of the PP@MXene-P@PDMS-NC composite film after hydrophobic agent modification under long-term water droplet retention.

[0030] Figure 6Testing and analysis of the bonding strength of the MXene-based conductive composite film before and after hydrophobic modification of the present invention; (a-c) show the change in the fastness of the PP@MXene-P composite film and the PP@MXene-P@PDMS-NC composite film under repeated friction with a fixed weight; (d) shows the mass loss change curve corresponding to the PP@MXene-P composite film and the PP@MXene-P@PDMS-NC composite film under repeated friction from 0 to 100 times; (e-f) show the effect of ultrasonic treatment on the structural stability of the PP@MXene-P composite film and the PP@MXene-P@PDMS-NC composite film.

[0031] Figure 7 Analysis of the conductivity (a) and electromagnetic shielding performance (b) of the MXene-based composite film after hydrophobic modification of the present invention;

[0032] Figure 8 Physical display diagrams of the hydrophobic effect of the hydrophobic composite film prepared by the present invention in different acid and alkali solutions and the lightweight characteristics of the hydrophobic composite film; (a) is a physical diagram of the pure MXene conductive film; (b) is a characterization of the lightweight characteristics of the PP@MXene-P@PDMS-NC composite film; (c) is a physical diagram of the foldable and bendable PP@MXene-P@PDMS-NC composite film and the change in the wettability of the PP@MXene-P@PDMS-NC composite film in a complex environment. Detailed implementation manners

[0033] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0034] The preparation methods of the MXene nanosheets, nanofiber membranes and MOF microspheres described in the present invention are all disclosed in the prior art. The following lists the conventional preparation methods of each material, and materials with a structure similar to the materials described in this application prepared by other methods can also be used in the present invention.

[0035] The preparation method of the MXene nanosheets is as follows: adding the precursor of Ti 3 C 2 T x to the etching agent for etching, and then centrifuging and washing the obtained solid to obtain the Ti 3 AlC 2 precipitate.

[0036] The precursor of the Ti 3 C 2 T x is Ti3 AlC 2 ; The etchant includes concentrated hydrochloric acid and lithium fluoride; the concentration of the concentrated hydrochloric acid is 9M, and the dosage of LiF is 0.025 - 0.1 g / mL of the concentrated hydrochloric acid. Ti 3 C 2 T x The mass ratio of the precursor of T to LiF is 1 - 2:1 - 2, and the precursor powder of Ti 3 C 2 T x is added to the etching solution in batches slowly, and the etching condition is to stir at 40 °C for 18 - 48 h.

[0037] Synthesis of MXene nanosheets with internal enhancement of PPy: Disperse MXene nanosheets in a certain amount of water, adjust the pH value of the MXene nanosheet solution to make it in a weakly acidic environment (pH = 5 - 7), add pyrrole, and continuously stir at 25 - 30 °C for 8 - 12 h to prepare MXene nanosheets assembled with PPy internally (MXene-PPy). The water is deionized water, distilled water or ultrapure water, and the pyrrole monomer used is from Aladdin Reagent (Shanghai) Co., Ltd.

[0038] The nanofiber membrane is prepared by electrospinning. Taking polyacrylonitrile (PAN) as an example: Dissolve PAN in N,N-dimethylformamide (DMF) to prepare a spinning solution with a concentration of 8% - 12%, and then through electrospinning technology, change the spinning time to prepare a PAN nanofiber membrane with controllable thickness. The spinning time is 30 min - 4 h.

[0039] Preparation of the MOF microspheres: Mix and react the metal precursor, ligand and solvent. The molar ratio of the ligand to the metal precursor is 0.2 - 2.0, and the molar ratio of the mixed solvent to the metal precursor is 0.1 - 4.0, and stir for 0 - 60 min; then transfer it to a reaction kettle lined with polytetrafluoroethylene and react at 80 - 160 °C for 12 - 36 h; filter, wash and dry for later use.

[0040] The metal precursor is any two of copper nitrate trihydrate, nickel nitrate hexahydrate, cobalt nitrate hexahydrate or cerium nitrate hexahydrate.

[0041] The ligand is trimesic acid, 2-methylimidazole or terephthalic acid.

[0042] The solvent is any two or three of N,N-dimethylformamide, deionized water or ethanol, and the volumes of the solvents are the same.

[0043] Example 1

[0044] A micro-nano dual-scale synergistically enhanced MXene-based conductive composite membrane, and its preparation method includes the following steps:

[0045] (1) Preparation of MXene-PPy nanosheets: In the first step, MXene nanosheets were synthesized. 1 g of LiF powder was added to 20 mL of HCl (9 M), and then the mixture was stirred at room temperature for 30 min to obtain the HCl / LiF mixture. Subsequently, 1 g of Ti 3 AlC 2 powder was added to the HCl / LiF mixture, and the mixture was continuously stirred at 40 °C for 24 h to completely etch away the Al layer. The obtained suspension was repeatedly washed with deionized water and centrifuged at 3500 rpm for 5 min until its pH value was approximately 6. Then, the black swollen clay-like precipitate was redispersed in deionized water and continuously sonicated in an ice-salt bath for 2 h, and then centrifuged at 3500 rpm for 1 h to ensure that the Ti 3 C 2 T x was completely delaminated. In the second step, the polymerization of pyrrole was achieved by utilizing the weak acidic property of the MXene nanosheet solution itself to prepare MXene nanosheets with internal enhancement modification of PPy. That is, 1 g of MXene nanosheets was redispersed in 15 ml of deionized water, and then 0.3 g of pyrrole monomer was slowly added dropwise to 5 ml of the MXene nanosheet solution, and the mixture was continuously stirred at room temperature for 12 h to prepare MXene nanosheets with internal assembly of PPy.

[0046] (2) Preparation of Ni-Co MOF: 0.216 g of Co(NO 3 ) 2 ·6H 2 O, 0.216 g of Ni(NO 3 ) 2 ·6H 2 O, 0.15 g of benzenetricarboxylic acid, and 1.5 g of PVP were respectively dissolved in 30 ml of a mixed solution (deionized water: ethanol: DMF = 1:1:1), and then magnetically stirred for 1 h to obtain a homogeneous mixed solution. Subsequently, the mixed solution was transferred to a 100 ml autoclave and maintained in an oven at 150 °C for 10 h. After cooling to room temperature, the purple product in the inner lining of the autoclave was washed 3 times with ethanol and placed in a vacuum drying oven at 70 °C for 12 h to obtain purple powder. The rotation speed during centrifugal washing was 4000 r / min, and the prepared sample was denoted as Ni-CoMOF (NC).

[0047] (3) Preparation of PDA-modified PAN nanofiber membrane: First, 2.2 g of PAN powder was added to 20 ml of N,N-dimethylformamide (DMF) solution, and stirred at room temperature for 6 h to obtain a uniform electrospinning mixed solution. Then, a PAN nanofiber membrane with a thickness of about 20 μm was prepared at a feeding rate of 0.8 mL / h, a voltage of 20 kV, a spinning distance of 17 cm, and a spinning time of 2 h. Next, 0.12 g of Tris-HCl and 0.2 g of DA were dissolved in 100 ml of deionized water, while 0.4 g of silane coupling agent (APTES) was dissolved in 20 ml of ethanol solution. Then the two solutions were mixed and stirred to prepare a DA / APTES mixed solution. Finally, the PAN membrane was placed in the DA / APTES mixed solution and soaked at room temperature for 12 h, and then the PDA-modified PAN membrane was rinsed several times with deionized water to remove surface impurities, obtaining a PDA-modified nanofiber membrane with excellent wetting properties.

[0048] (4) Preparation of PPy-reinforced MXene-based nanofiber membrane: The MXene-PPy nanosheets (1 g) prepared in step (1) were dispersed in 100 ml of deionized water and shaken by hand to make them evenly distributed. Then, the PDA-modified PAN nanofiber (PP) membrane was placed on the upper layer of the PVDF filter hydrophilic membrane (pore size 0.22 μm), and a MXene-PPy conductive layer was constructed through a vacuum-assisted suction filtration device, thereby preparing a PPy-reinforced MXene-based nanofiber membrane. For convenience of description, this conductive layer was defined as the upper conductive layer on the surface of the PP substrate.

[0049] (5) Preparation of a dual-scale synergistically modified MXene-based conductive composite membrane: 0.03 g of Ni-CoMOF synthesized in step (2) was added to 20 ml of PDMS (4 wt%) solution, and ultrasonically dispersed for 2 h to ensure that the Ni-Co MOF microspheres were as evenly dispersed as possible in the silicone-based hydrophobic agent. Then, the PPy-reinforced MXene-based nanofiber membrane prepared in step (3) was placed in the PDMS / Ni-Co MOF mixed solution, impregnated for 50 min, and then air-dried and stored, finally preparing a dual-scale modified MXene-based nano-conductive composite membrane.

[0050] Example 2

[0051] A micro-nano dual-scale synergistically reinforced MXene-based conductive composite membrane, and its preparation method includes the following steps:

[0052] (1) Preparation of MXene-PPy nanosheets: In the first step, MXene nanosheets were first synthesized. 1 g of LiF powder was added to 20 mL of HCl (9M), and then stirred at room temperature for 30 min to obtain an HCl / LiF mixture. Then, 1 g of Ti 3AlC 2 The powder was added to the HCl / LiF mixture, and the mixture was continuously stirred at 40 °C for 24 h to completely etch away the Al layer. The obtained suspension was washed repeatedly with deionized water and centrifuged at 3500 rpm for 5 min until its pH value was about 6. Then, the black swollen clay-like precipitate was redispersed in deionized water and continuously sonicated in an ice-salt bath for 2 h, and then centrifuged at 3500 rpm for 1 h to ensure that the used Ti 3 C 2 Tx was completely delaminated. In the second step, the polymerization of pyrrole was achieved by using the weak acidic property of the MXene nanosheet solution itself to prepare MXene nanosheets with internal enhanced modification of PPy. That is, 1 g of MXene nanosheets was redispersed in 15 ml of deionized water, and then 0.3 g of pyrrole monomer was slowly added dropwise to 5 ml of the MXene nanosheet solution, and continuously stirred at room temperature for 12 h to prepare MXene nanosheets with internal assembly of PPy.

[0053] (2) Preparation of Ni-Co MOF: 0.216 g of Co(NO 3 ) 2 ·6H 2 O, 0.216 g of Ni(NO 3 ) 2 ·6H 2 O, 0.15 g of benzenetricarboxylic acid and 1.5 g of PVP were respectively dissolved in 30 ml of a mixed solution (deionized water: ethanol: DMF = 1:1:1), and then magnetically stirred for 1 h to obtain a homogeneous mixed solution. Then the mixed solution was transferred to a 100 ml autoclave and kept in an oven at 150 °C for 10 h. After cooling to room temperature, the purple product in the inner liner of the autoclave was washed 3 times with ethanol and placed in a vacuum drying oven at 70 °C for 12 h to obtain purple powder. The rotation speed during centrifugal washing was 4000 r / min, and the prepared sample was denoted as Ni-CoMOF (NC).

[0054] (3) Preparation of PDA-modified PAN nanofiber membrane: First, 2.2 g of PAN powder was added to 20 ml of N,N-dimethylformamide (DMF) solution and stirred at room temperature for 6 h to obtain a uniform electrospinning mixed solution. Then, a PAN nanofiber membrane with a thickness of about 20 μm was prepared at a feeding rate of 0.8 mL / h, a voltage of 20 kV, a spinning distance of 17 cm, and a spinning time of 2 h. Next, 0.12 g of Tris-HCl and 0.2 g of DA were dissolved in 100 ml of deionized water, and at the same time, 0.4 g of silane coupling agent (APTES) was dissolved in 20 ml of ethanol solution. Then the two solutions were mixed and stirred to prepare a DA / APTES mixed solution. Finally, the PAN membrane was placed in the DA / APTES mixed solution and soaked at room temperature for 12 h, and then the PDA-modified PAN membrane was rinsed several times with deionized water to remove surface impurities, obtaining a PDA-modified nanofiber membrane with excellent wetting properties.

[0055] (4) Preparation of PPy-reinforced MXene-based nanofiber membrane: The MXene-PPy nanosheets (1 g) prepared in step (1) were dispersed in 100 ml of alcohol solution and shaken by hand to make them evenly distributed. Then, the PDA-modified PAN nanofiber (PP) membrane was placed on the upper layer of the PVDF filter hydrophobic membrane (pore size 0.22 μm), and a MXene-PPy conductive layer was constructed through a vacuum-assisted suction filtration device, thereby preparing a PPy-reinforced MXene-based nanofiber membrane. For convenience of description, this conductive layer was defined as the lower conductive layer on the surface of the PP substrate.

[0056] (5) Preparation of a dual-scale synergistically modified MXene-based conductive composite membrane: 0.03 g of Ni-CoMOF synthesized in step (2) was added to 20 ml of PDMS (4 wt%) solution, and ultrasonically dispersed for 2 h to ensure that the Ni-Co MOF microspheres were as evenly dispersed as possible in the silicone-based water repellent. Then, the PPy-reinforced MXene-based nanofiber membrane prepared in step (3) was placed in the PDMS / Ni-Co MOF mixed solution, impregnated for 50 min, and then dried and stored, finally preparing a dual-scale modified MXene-based nano-conductive composite membrane.

[0057] Example 3

[0058] A micro-nano dual-scale synergistically reinforced MXene-based conductive composite membrane, and its preparation method includes the following steps:

[0059] (1) Preparation of MXene-PPy nanosheets: In the first step, MXene nanosheets were first synthesized. 1 g of LiF powder was added to 20 mL of HCl (9M), and then stirred at room temperature for 30 min to obtain a HCl / LiF mixture. Then, 1 g of Ti 3AlC 2 The powder was added to the HCl / LiF mixture, and the mixture was continuously stirred at 40 °C for 24 h to completely etch away the Al layer. The obtained suspension was repeatedly washed with deionized water and centrifuged at 3500 rpm for 5 min until its pH value was about 6. Then, the black swollen clay-like precipitate was redispersed in deionized water and continuously sonicated in an ice-salt bath for 2 h, and then centrifuged at 3500 rpm for 1 h to ensure the complete stratification of the used Ti 3 C 2 Tx. In the second step, the polymerization of pyrrole was realized by using the weak acidic property of the MXene nanosheet solution itself, and the MXene nanosheets modified by internal reinforcement of PPy were prepared. That is, 1 g of MXene nanosheets were redispersed in 15 ml of deionized water, and then 0.3 g of pyrrole monomer was slowly added dropwise to 5 ml of the MXene nanosheet solution, and continuously stirred at room temperature for 12 h to prepare the MXene nanosheets with PPy internally assembled.

[0060] (2) Preparation of Ni-Co MOF: 0.216 g of Co(NO 3 ) 2 ·6H 2 O, 0.216 g of Ni(NO 3 ) 2 ·6H 2 O, 0.15 g of benzenetricarboxylic acid and 1.5 g of PVP were respectively dissolved in 30 ml of a mixed solution (deionized water: ethanol: DMF = 1:1:1), and then magnetically stirred for 1 h to obtain a uniform mixed solution. Then, the mixed solution was transferred to a 100 ml autoclave and kept in an oven at 150 °C for 10 h. After cooling to room temperature, the purple product in the inner lining of the reaction kettle was washed 3 times with ethanol and placed in a vacuum drying oven at 70 °C for 12 h to obtain purple powder. The rotation speed during centrifugal washing was 4000 r / min, and the prepared sample was denoted as Ni-CoMOF (NC).

[0061] (3) Preparation of PDA-modified PAN nanofiber membrane: First, 2.2 g of PAN powder was added to 20 ml of N,N-dimethylformamide (DMF) solution and stirred at room temperature for 6 h to obtain a uniform electrospinning mixed solution. Then, a PAN nanofiber membrane with a thickness of about 20 μm was prepared at a feeding rate of 0.8 mL / h, a voltage of 20 kV, a spinning distance of 17 cm, and a spinning time of 2 h. Next, 0.12 g of Tris-HCl and 0.2 g of DA were dissolved in 100 ml of deionized water, and at the same time, 0.4 g of silane coupling agent (APTES) was dissolved in 20 ml of ethanol solution. Then the two solutions were mixed and stirred to prepare a DA / APTES mixed solution. Finally, the PAN membrane was placed in the DA / APTES mixed solution and soaked at room temperature for 12 h, and then the PDA-modified PAN membrane was rinsed several times with deionized water to remove surface impurities, obtaining a PDA-modified nanofiber membrane with excellent wetting properties.

[0062] (4) Preparation of PPy-reinforced MXene-based nanofiber membrane: The MXene-PPy nanosheets (1 g) prepared in step (1) were dispersed in 100 ml of deionized water and shaken by hand to make them evenly distributed. Then, the PDA-modified PAN nanofiber (PP) membrane was placed on the upper layer of the PVDF hydrophilic membrane, and a MXene conductive layer was prepared through a vacuum-assisted filtration device. For convenience of description, this conductive layer is defined as the upper conductive layer on the surface of the PP substrate. In addition, to construct the lower conductive layer of the PP substrate, the MXene-PPy nanosheets were dispersed in 100 ml of alcohol solution. The previously prepared substrate with the upper conductive layer was placed on the PVDF hydrophobic membrane, and then the MXene-PPy mixed solution dispersed in the alcohol solution was combined with the lower surface of the PP substrate according to the previous preparation process, finally preparing a composite membrane with MXene-PPy (MXene-P) conductive layers on both the upper and lower surfaces. Among them, for convenience of description, PP@MXene-P’ represents the composite membrane with the upper conductive layer; PP@MXene-P” represents the composite membrane with only the lower conductive layer; PP@MXene-P represents the composite membrane with both the upper and lower conductive layers. It should be noted that: after preparing the upper conductive layer by filtration, to successfully construct the lower conductive layer, the MXene-PPy nanosheets need to be dispersed in the alcohol solution, and at the same time, the hydrophilic PVDF membrane is replaced with a hydrophobic PVDF membrane. This is mainly because alcohol can penetrate through the hydrophobic PVDF membrane and intercept the MXene-PPy nanosheets on the lower surface of the PAN-PDA substrate, and will not damage the conductive layer on the upper surface of the PAN-PDA substrate.

[0063] (5) Preparation of a dual-scale synergistically modified MXene-based conductive composite film: Add the Ni-CoMOF (0.03 g) synthesized in step (2) into 20 ml of PDMS (4 wt%) solution, and ultrasonically disperse it for 2 h to ensure that the Ni-Co MOF microspheres are as evenly dispersed as possible in the silicone-based water repellent. Then, place the PPy-reinforced MXene-based nanofiber membrane prepared in step (3) in the PDMS / Ni-Co MOF mixed solution, impregnate it for 50 min, and then air-dry and store it to finally prepare a dual-scale modified MXene-based nano-conductive composite film.

[0064] Example 4

[0065] A micro-nano dual-scale synergistically reinforced MXene-based conductive composite film, and its preparation method includes the following steps:

[0066] (1) Preparation of MXene-PPy nanosheets: In the first step, synthesize MXene nanosheets first. Add 1 g of LiF powder to 20 mL of HCl (9M), and then stir at room temperature for 30 min to obtain an HCl / LiF mixture. Next, add 1 g of Ti 3 AlC 2 powder to the HCl / LiF mixture, and continuously stir the mixture at 40 °C for 24 h to completely etch away the Al layer. Wash the obtained suspension repeatedly with deionized water, and centrifuge it at 3500 rpm for 5 min until its pH value is about 6. Then, redisperse the black swollen clay-like precipitate in deionized water and continuously ultrasonicate it in an ice-salt bath for 2 h, and then centrifuge it at 3500 rpm for 1 h to ensure that the used Ti 3 C 2 Tx is completely delaminated. In the second step, utilize the weak acidic property of the MXene nanosheet solution itself to achieve the polymerization of pyrrole, and prepare MXene nanosheets with internal PPy reinforcement modification. That is, redisperse 1 g of MXene nanosheets in 10 ml of deionized water, and then slowly drop 0.5 g of pyrrole monomer into 5 ml of the MXene nanosheet solution, and continuously stir at room temperature for 12 h to prepare MXene nanosheets with internal PPy assembly.

[0067] (2) Preparation of Ni-Co MOF: Add 0.216 g of Co(NO 3 ) 2 ·6H 2 O, 0.216 g of Ni(NO 3 ) 2 ·6H 20.15 g of benzene tricarboxylic acid and 1.5 g of PVP were separately dissolved in 30 ml of a mixed solution (deionized water: ethanol: DMF = 1:1:1), and then magnetically stirred for 1 h to obtain a homogeneous mixed solution. Subsequently, the mixed solution was transferred to a 100 ml autoclave and maintained in an oven at 150 °C for 10 h. After cooling to room temperature, the purple product in the inner lining of the autoclave was washed three times with ethanol and placed in a vacuum drying oven at 70 °C for 12 h to obtain purple powder. The rotation speed during centrifugal washing was 4000 r / min, and the prepared sample was denoted as Ni-CoMOF (NC).

[0068] (3) Preparation of PDA-modified PAN nanofiber membrane: First, 2.2 g of PAN powder was added to 20 ml of N,N-dimethylformamide (DMF) solution and stirred at room temperature for 6 h to obtain a homogeneous electrospinning mixed solution. Then, a PAN nanofiber membrane with a thickness of approximately 20 μm was prepared at a feeding rate of 0.8 mL / h, a voltage of 20 kV, a spinning distance of 17 cm, and a spinning time of 2 h. Next, 0.12 g of Tris-HCl and 0.2 g of DA were dissolved in 100 ml of deionized water, and at the same time, 0.5 g of silane coupling agent (APTES) was dissolved in 20 ml of ethanol solution. Then the two solutions were mixed and stirred to prepare a DA / APTES mixed solution. Finally, the PAN membrane was placed in the DA / APTES mixed solution and soaked at room temperature for 6 h, and then the PDA-modified PAN membrane was rinsed several times with deionized water to remove surface impurities, obtaining a PDA-modified nanofiber membrane with excellent wetting properties.

[0069] (4) Preparation of PPy-reinforced MXene-based nanofiber membrane: Disperse the MXene-PPy nanosheets (1 g) prepared in step (1) in 100 ml of deionized water and shake it manually to make it evenly distributed. Then, place the PDA-modified PAN nanofiber (PAN-P) membrane on the upper layer of the PVDF hydrophilic membrane, and prepare the MXene conductive layer through a vacuum-assisted filtration device. For convenience of description, this conductive layer is defined as the upper conductive layer on the surface of the PAN-P substrate. Additionally, to construct the lower conductive layer of the PP substrate, disperse the MXene-PPy nanosheets in 100 ml of alcohol solution. Place the previously prepared substrate with the upper conductive layer on the PVDF hydrophobic membrane, and then combine the MXene-PPy mixed solution dispersed in the alcohol solution with the lower surface of the PP substrate according to the previous preparation process, and finally prepare a composite membrane with MXene-PPy (MXene-P) conductive layers on both the upper and lower surfaces. Among them, for convenience of description, PP@MXene-P’ represents the composite membrane with the upper conductive layer; PP@MXene-P” represents the composite membrane with only the lower conductive layer; PP@MXene-P represents the composite membrane with both upper and lower conductive layers. It should be noted that: after preparing the upper conductive layer by filtration, to successfully construct the lower conductive layer, the MXene-PPy nanosheets need to be dispersed in the alcohol solution, and at the same time, the hydrophilic PVDF membrane is replaced with a hydrophobic PVDF membrane. This is mainly because alcohol can penetrate through the hydrophobic PVDF membrane and intercept the MXene-PPy nanosheets on the lower surface of the PAN-PDA substrate, and will not damage the conductive layer on the upper surface of the PAN-PDA substrate.

[0070] (5) Preparation of a dual-scale synergistically modified MXene-based conductive composite membrane: Add the Ni-CoMOF (0.04 g) synthesized in step (2) into 20 ml of PDMS (0.5 wt%) solution, and ultrasonically disperse it for 2 h to ensure that the Ni-Co MOF microspheres are as evenly dispersed as possible in the silicone-based water repellent. Then, place the PPy-reinforced MXene-based nanofiber membrane prepared in step (2) in the PDMS / Ni-Co MOF mixed solution, impregnate it for 50 min, and then dry it for storage. Finally, a dual-scale modified MXene-based nano-conductive composite membrane is prepared.

[0071] Example 5

[0072] A micro-nano dual-scale synergistically reinforced MXene-based conductive composite membrane, and its preparation method includes the following steps:

[0073] (1) Preparation of MXene-PPy nanosheets: First, synthesize MXene nanosheets. Add 1 g of LiF powder to 20 mL of HCl (9M), and then stir it at room temperature for 30 min to obtain the HCl / LiF mixture. Then, add 1 g of Ti 3AlC 2 The powder was added to the HCl / LiF mixture, and the mixture was continuously stirred at 40 °C for 24 h to completely etch away the Al layer. The obtained suspension was washed repeatedly with deionized water and centrifuged at 3500 rpm for 5 min until its pH value was about 6. Then, the black swollen clay-like precipitate was redispersed in deionized water and continuously sonicated in an ice-salt bath for 2 h, and then centrifuged at 3500 rpm for 1 h to ensure the complete stratification of the used Ti 3 C 2 Tx. In the second step, the polymerization of pyrrole was realized by using the weak acidic property of the MXene nanosheet solution itself to prepare MXene nanosheets with internal enhancement modification of PPy. That is, 1 g of MXene nanosheets was redispersed in 100 ml of deionized water, and then 0.1 g of pyrrole monomer was slowly added dropwise to 5 ml of the MXene nanosheet solution, and continuously stirred at room temperature for 12 h to prepare MXene nanosheets with internal assembly of PPy.

[0074] (2) Preparation of Ni-Co MOF: 0.216 g of Co(NO 3 ) 2 ·6H 2 O, 0.216 g of Ni(NO 3 ) 2 ·6H 2 O, 0.15 g of benzenetricarboxylic acid and 1.5 g of PVP were respectively dissolved in 30 ml of a mixed solution (deionized water: ethanol: DMF = 1:1:1), and then magnetically stirred for 1 h to obtain a homogeneous mixed solution. Then, the mixed solution was transferred to a 100 ml autoclave and kept in an oven at 150 °C for 10 h. After cooling to room temperature, the purple product in the inner lining of the reaction kettle was washed 3 times with ethanol and placed in a vacuum drying oven at 70 °C for 12 h to obtain purple powder. The rotation speed during centrifugal washing was 4000 r / min, and the prepared sample was denoted as Ni-CoMOF (NC).

[0075] (3) Preparation of PDA-modified PAN nanofiber membrane: First, 2.2 g of PAN powder was added to 20 ml of N,N-dimethylformamide (DMF) solution and stirred at room temperature for 6 h to obtain a uniform electrospinning mixed solution. Then, a PAN nanofiber membrane with a thickness of about 20 μm was prepared at a feeding rate of 0.8 mL / h, a voltage of 20 kV, a spinning distance of 17 cm, and a spinning time of 2 h. Next, 0.12 g of Tris-HCl and 0.2 g of DA were dissolved in 100 ml of deionized water, and at the same time, 0.2 g of silane coupling agent (APTES) was dissolved in 20 ml of ethanol solution. Then the two solutions were mixed and stirred to prepare a DA / APTES mixed solution. Finally, the PAN membrane was placed in the DA / APTES mixed solution and soaked at room temperature for 1 h, and then the PDA-modified PAN membrane was rinsed several times with deionized water to remove surface impurities, obtaining a PDA-modified nanofiber membrane with excellent wetting properties.

[0076] (4) Preparation of PPy-reinforced MXene-based nanofiber membrane: The MXene-PPy nanosheets (0.5 g) prepared in step (1) were dispersed in 100 ml of deionized water and shaken by hand to make them evenly distributed. Next, the PDA-modified PAN nanofiber (PAN-P) membrane was placed on the upper layer of the PVDF hydrophilic membrane, and a MXene conductive layer was prepared through a vacuum-assisted filtration device. For convenience of description, this conductive layer was defined as the upper conductive layer on the surface of the PAN-P substrate. In addition, to construct the lower conductive layer of the PP substrate, the MXene-PPy nanosheets were dispersed in 100 ml of alcohol solution. The previously prepared substrate with the upper conductive layer was placed on the PVDF hydrophobic membrane, and then the MXene-PPy mixed solution dispersed in the alcohol solution was combined with the lower surface of the PP substrate according to the previous preparation process, finally preparing a composite membrane with MXene-PPy (MXene-P) conductive layers on both the upper and lower surfaces. Among them, for convenience of description, PP@MXene-P’ represents the composite membrane with the upper conductive layer; PP@MXene-P” represents the composite membrane with only the lower conductive layer; PP@MXene-P represents the composite membrane with both the upper and lower conductive layers. It should be noted that: after preparing the upper conductive layer by filtration, to successfully construct the lower conductive layer, the MXene-PPy nanosheets need to be dispersed in the alcohol solution, and at the same time, the hydrophilic PVDF membrane is replaced with a hydrophobic PVDF membrane. This is mainly because alcohol can penetrate through the hydrophobic PVDF membrane and intercept the MXene-PPy nanosheets on the lower surface of the PAN-PDA substrate, and will not damage the conductive layer on the upper surface of the PAN-PDA substrate.

[0077] (5) Preparation of a double-scale synergistically modified MXene-based conductive composite membrane: Add the Ni-CoMOF (0.01 g) synthesized in step (2) into 20 ml of a PDMS (0.5 wt%) solution, and ultrasonically disperse it for 2 h to ensure that the Ni-Co MOF microspheres are as uniformly dispersed as possible in the silicone-based water repellent. Then, place the PPy-reinforced MXene-based nanofiber membrane prepared in step (2) in the PDMS / Ni-Co MOF mixed solution, immerse it for 50 min, and then air-dry and store it to finally obtain a double-scale modified MXene-based nano-conductive composite membrane.

[0078] Comparative Example 1

[0079] Pure MXene conductive membrane, its preparation method: First, add 1 g of LiF powder to 20 mL of HCl (9 M), and then stir at room temperature for 30 min to obtain an HCl / LiF mixture. Next, add 1 g of Ti 3 AlC 2 powder to the HCl / LiF mixture, and continuously stir the mixture at 40 °C for 24 h to completely etch away the Al layer. Wash the obtained suspension repeatedly with deionized water, and centrifuge it at 3500 rpm for 5 min until its pH value is about 6. Then, redisperse the black swollen clay-like precipitate in deionized water and continuously ultrasonicate it in an ice-salt bath for 2 h, and then centrifuge it at 3500 rpm for 1 h to ensure that the used Ti 3 C 2 Tx is completely delaminated. Finally, use the vacuum-assisted filtration technique to prepare a pure MXene conductive membrane. That is, disperse 1 g of MXene nanosheets prepared by etching in 50 ml of deionized water, prepare a pure MXene membrane through a vacuum filtration device, and then place it in an oven at 50 °C for 30 min to obtain a pure MXene conductive membrane.

[0080] Comparative Example 2

[0081] PPy-reinforced MXene-based nanofiber membrane, its preparation method:

[0082] (1) Preparation of MXene-PPy nanosheets: The first step is to synthesize MXene nanosheets. Add 1 g of LiF powder to 20 mL of HCl (9 M), and then stir at room temperature for 30 min to obtain an HCl / LiF mixture. Next, add 1 g of Ti 3 AlC 2The powder was added to the HCl / LiF mixture, and the mixture was continuously stirred at 40 °C for 24 h to completely etch away the Al layer. The obtained suspension was repeatedly washed with deionized water and centrifuged at 3500 rpm for 5 min until its pH value was about 6. Then, the black swollen clay-like precipitate was redispersed in deionized water and continuously sonicated in an ice-salt bath for 2 h, and then centrifuged at 3500 rpm for 1 h to ensure complete delamination of the Ti 3 C 2 Tx. In the second step, the polymerization of pyrrole was achieved by utilizing the weak acidic property of the MXene nanosheet solution itself to prepare MXene nanosheets internally reinforced and modified with PPy. That is, 1 g of MXene nanosheets was redispersed in 15 ml of deionized water, and then 0.3 g of pyrrole monomer was slowly added dropwise to 5 ml of the MXene nanosheet solution, and continuously stirred at room temperature for 12 h to prepare MXene nanosheets with PPy internally assembled.

[0083] (2) Preparation of PPy-reinforced MXene-based nanofiber membrane: The MXene-PPy nanosheets prepared in step (1) were dispersed in an appropriate amount of deionized water and shaken by hand to make them evenly distributed. Then, the PDA-modified PAN nanofiber (PAN-P) membrane was placed on the upper layer of the PVDF hydrophilic membrane, and the MXene conductive layer was prepared through a vacuum-assisted filtration device. For convenience of description, this conductive layer is defined as the upper conductive layer on the surface of the PAN-P substrate. In addition, to construct the lower conductive layer of the PAN-P substrate, the MXene-PPy nanosheets were dispersed in an alcohol solution. The previously prepared substrate with the upper conductive layer was placed on the PVDF hydrophobic membrane, and then the MXene-PPy mixed solution dispersed in the alcohol solution was combined with the lower surface of the PAN-P substrate according to the previous preparation process, and finally a composite membrane with MXene-PPy (MXene-P) conductive layers on both the upper and lower surfaces was prepared. Among them, for convenience of description, "PP@MXene-P'" represents the composite membrane with the upper conductive layer; "PP@MXene-P"" represents the composite membrane with only the lower conductive layer; "PP@MXene-P" represents the composite membrane with both the upper and lower conductive layers. It should be noted that: after preparing the upper conductive layer by filtration, to successfully construct the lower conductive layer, the MXene-PPy nanosheets need to be dispersed in an alcohol solution, and at the same time, the hydrophilic PVDF membrane is replaced with a hydrophobic PVDF membrane. This is mainly because alcohol can penetrate through the hydrophobic PVDF membrane and retain the MXene-PPy nanosheets on the lower surface of the PAN-PDA substrate without damaging the conductive layer on the upper surface of the PAN-PDA substrate.

[0084] Test example

[0085] The samples prepared in Examples 1-3 were characterized and tested. First, it should be noted that the samples prepared during the preparation process according to the above-mentioned examples were labeled. In Examples 1-3, MXene-PPy represents MXene nanosheets assembled inside PPy; the dopamine-modified polyacrylonitrile nanofiber membrane is denoted as PP, the composite membrane with an upper conductive layer is denoted as PP@MXene-P’ (Example 1), the composite membrane with a lower conductive layer is denoted as PP@MXene-P” (Example 2), and the sample prepared after the synergistic hydrophobic modification of PDMS and Ni-Co MOF is denoted as PP@MXene-P@PDMS-NC (Example 3). The above sample names correspond to the figure descriptions in the following figures.

[0086] Figure 1 It is a preparation method for a MXene-based conductive composite membrane with dual-scale synergistic enhancement. Figure 1 (a) is the preparation flow chart of PPy-assembled MXene nanosheets. Figure 1 (b) is the preparation flow chart of the PP@MXene-P@PDMS-NC conductive composite membrane.

[0087] Figures 2 - 5 For the testing of the samples prepared in each step of Example 3, from Figure 2 (a-d), it can be observed that polypyrrole nanoparticles (PPy) are uniformly dispersed at the edges of MXene nanosheets to form a PPy protective layer, which can effectively prevent oxidative degradation at the edges of MXene nanosheets. The SEM image of the cross-section of the pure MXene-P film shows that the conductive film formed by PPy-doped MXene nanosheets still exhibits a rock-like tightly packed layered structure. Figure 2 (e) shows that MXene-PPy nanosheets have excellent antibacterial properties against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), and the antibacterial property is as high as 95%. This antibacterial test was carried out according to the American standard ASTM E2149. E. coli and S. aureus were cultured in soy peptone broth, and the samples were sterilized before the antibacterial test.

[0088] From Figure 3 (a), it can be seen that the MXene nanosheets before and after PPy doping show two platforms and a mass mutation region. Compared with MXene nanosheets, the temperature at which the MXene-PPy nanosheets undergo a weight gain reaction increases from the original 352 °C to 409 °C, indicating that the doping of PPy is beneficial to improving the structural stability of MXene nanosheets. In addition, from Figure 3 (b), it can be seen that the internal doping of MXene nanosheets in PPy does not change the crystal structure change of MXene nanosheets, and there is no obvious exothermic peak in the MXene nanosheets before and after modification at 50-600 °C.

[0089] From Figure 4 the SEM images of (a - b), it can be seen that the prepared Ni - Co MOF presents a dandelion - like microsphere structure, and the surface of the microsphere is composed of countless nanosized fine rods arranged disorderly. The XRD and XPS testing techniques were used to further study the chemical structure of Ni - CoNOF. In the XRD pattern of Ni - Co MOF, the characteristic peaks are sharp, indicating its good crystallinity ( Figure 4 (c)). The characteristic peaks at 2θ = 9.2 and 2θ = 12.6 belong to the (100) and (003) crystal planes of Ni - Co MOF, respectively. Figure 4 The XPS results of (d) show that C, O, N, Co, and Ni elements exist on the surface of Ni - Co MOF.

[0090] From Figure 5 (a - b), it can be seen that the MXene conductive layers are uniformly deposited on the upper and lower surfaces of the PP@MXene - P membrane. Moreover, the dispersion of MXene nanosheets in water or alcohol does not affect the hydrophilicity of the MXene - PPy conductive layer. The contact angles of the upper and lower surfaces of the PP@MXene - P membrane are 79° and 75° respectively ( Figure 5 (c)). From Figure 5 as shown in (d), the presence of the hydrophobic layer does not destroy the conductive structure of the composite membrane, but forms a hydrophobic protection layer on the upper and lower surfaces of the conductive layer. Figure 5 (e - e'') shows the surface micro - morphology of the PP@MXene - P@PDMS - NC composite membrane. The silicon - containing hydrophobic agent wrapped on the surface of the NC microspheres covers the original nanosized fine rods on the surface of the microspheres, and a large number of NC microspheres exist on the surface of the MXene conductive layer, enhancing the hydrophobic effect of the composite membrane surface. From Figure 5 (f), it can be seen that the initial CA of PP@MXene - P@PDMS - NC is 138.99°. When water droplets remain on the surface of the hydrophobic composite membrane for a long time, the contact angle will decrease.

[0091] The double - scale modified MXene - based nano - conductive composite membrane prepared in Example 3 and the specimen prepared in Comparative Example 2 were made into samples, and the binding fastness of the conductive layer was tested by repeatedly rubbing with a cotton fabric under a fixed weight (20 g weight) for 100 times and ultrasonically treating the MXene - based conductive composite membrane for 2 h. From Figure 6 (a - c), it can be seen that for the composite membrane without hydrophobic treatment in Comparative Example 2, there are a large number of residual MXene - P conductive particles on the surface of the cotton fabric after continuous rubbing. For the composite membrane after hydrophobic modification, when the number of rubbing times reaches 100 times, only a small amount of black particles fall off on the surface of the cotton fabric. Figure 6(d) It can be seen that when the friction number is 100 times, the mass loss rate of the PP@MXene-P composite film is reduced to 89.43% compared with the initial mass loss rate. However, when the PP@MXene-P@PDMS-NC composite film is rubbed back and forth 100 times, the mass loss rate only decreases from the initial 100% to 95.73%. In addition, Figure 6 (ef) It can be seen that the PP@MXene-P@PDMS-NC composite film has good structural stability. After ultrasonic treatment, the black conductive particles did not fall off significantly, and the aqueous solution remained clear and transparent. The above experiments confirmed that the conductive composite film modified with multiple functional layers has a stable structure and can meet the requirements of continuous friction and bending in actual use.

[0092] Depend on Figure 7 (a) It can be seen that both the upper and lower surfaces of the PP@MXene-P composite film have excellent conductivity. After 2h of hydrophobic and ultrasonic treatment, the conductivity of the PP@MXene-P composite film will be reduced to a certain extent, but the composite film still has an excellent conductive network and can effectively shield the incident electromagnetic waves. Figure 7 (b) It can be seen that the PP@MXene-P composite film has excellent electromagnetic shielding performance (EMI SE), with a value of up to 44.50dB, which can effectively attenuate 99.99% of electromagnetic waves. The EMI SE values ​​of the composite film after hydrophobic and ultrasonic treatment are 38.75dB and 33.90dB, respectively, which can still effectively shield the incident electromagnetic waves.

[0093] Depend on Figure 8 (a) It can be seen that the pure MXene film prepared in Comparative Example 1 is fragile and has poor mechanical properties, which is difficult to meet the actual use as a shielding material. Figure 8 (b) It can be seen that when the PP@MXene-P@PDMS-NC composite film is gently placed on the young leaves of the plant, no obvious bending is found, indicating that the PPy internally doped MXene-based conductive composite film has good flexibility and lightness and can be flexibly used in various environments. Figure 8 (c) It can be seen that the presence of the silicon-containing hydrophobic layer can make water droplets in different acid and alkaline environments stay on the surface of the composite membrane. When the residence time is 20 minutes, the water droplets still have a good shape and do not spread on the surface of the composite membrane.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a micro-nano dual-scale synergistically enhanced MXene-based conductive composite film, characterized in that: The following steps are involved: (1) Pyrrole monomer was added dropwise to the MXene solution to prepare MXene nanosheets doped with PPy, which were referred to as MXene-PPy nanosheets. (2) Loading MXene-PPy nanosheets onto nanofiber membranes to prepare MXene-based nanofiber conductive membranes; (3) The MOF microspheres are mixed with a hydrophobic agent to prepare a hydrophobic solution, and the MXene-based nanofiber conductive membrane is immersed in the hydrophobic solution to prepare a micro-nano dual-scale synergistically enhanced MXene-based conductive composite membrane with a hydrophobic effect.

2. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 1, characterized in that: The mass ratio of the pyrrole monomer to the MXene is 1:(0.5-2); the concentration of the MXene in the MXene solution is 0.01-0.1 g / ml.

3. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 1, characterized in that: The nanofiber membrane is any one of polyacrylonitrile, polyurethane or thermoplastic polyurethane nanofiber membrane.

4. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 3, characterized in that: The nanofiber membrane is a nanofiber membrane modified with polydopamine, and the modification method is: immersing the nanofiber membrane in a solution containing DA to make the DA polymerize.

5. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 4, characterized in that: The conditions of the DA polymerization reaction are pH=8-9 and the polymerization time is 0-12h.

6. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 1, characterized in that: In the step (2), the MXene-PPy nanosheets are loaded on at least one surface of the nanofiber membrane; the loading method is suction filtration.

7. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 2, characterized in that: In the step (2), the MXene-PPy nanosheets are filtered on both sides of the nanofiber membrane. The preparation method is as follows: dispersing the MXene-PPy nanosheets in a solvent to prepare a suspension, placing the nanofiber membrane on a hydrophilic support membrane for filtering, and the MXene-PPy nanosheets are deposited on one side of the nanofiber membrane to form an upper conductive layer; then the nanofiber membrane is turned over and placed on a hydrophobic support membrane for filtering, and the MXene-PPy nanosheets are deposited on the other side of the nanofiber membrane to form a lower conductive layer.

8. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 1, characterized in that: The MOF microspheres are Ni-Co MOF microspheres; the hydrophobic agent is a silicon-containing hydrophobic agent; and the silicon-containing hydrophobic agent is polydimethylsiloxane.

9. The method for preparing the micro-nano dual-scale synergistically enhanced MXene-based conductive composite film according to claim 8, characterized in that: The concentration of the hydrophobic agent in the hydrophobic solution is 0.5-4 wt %, and the concentration of the MOF microspheres is 0.1-2 mg / ml.

10. A micro-nano dual-scale synergistically enhanced MXene-based conductive composite film prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flexible nanofiber membrane with electromagnetic shielding and piezoresistive sensing performance and preparation method thereof

    CN114150496A

Cited By

  • PO film with good cooling effect in summer and preparation method thereof

    CN120966070A

  • MXene / PPy / filter paper composite film, preparation method thereof and water evaporation power generation device

    CN122502690A